Performing rock ballad music on the lead guitar : issues and problems looked by present day guitar understudies in the Faculty of Music UiTM / Syahrul Dini Azmi - Azmi, Syahrul Dini (2019)
Every guitarist who played rock ballad music on the lead guitar especially when on live performance wanted to achive a good tone production, being able to deliver the melody to the audience. This research examines the daily exercise for every guitarist, a problem or technical difficulties during live performance and an advised and a tips from professional guitarist around Kuala Lumpur and Klang Valley. This research will be looking on 3 main objective which is to explore how lead guitar players build up their abilities in interpreting music, to portray what are the difficulties and problems looked by lead guitar when interpret music and to investigate what should lead guitar players practice in their daily routines.